Analisis Kesulitan Siswa dalam Pemecahan Masalah Matematika di Sekolah Menengah Pertama - Joefanny, Laras; Annas, Muhammad Khairul; Pratama, Muhammad Arif; Fauzi, Amin (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to analyze the difficulties experienced by junior high school students in solving mathematical problems, especially related to solving arithmetic and geometry problems. This study uses a qualitative descriptive approach. The research subjects consisted of 50 grade VIII students at a junior high school in Delitua. Data was collected through problem-solving tests and in-depth interviews. The results of the study show that the main difficulties of students in solving mathematical problems are understanding basic concepts, choosing problem-solving strategies, and misinterpreting problems. This difficulty is generally caused by a lack of understanding of basic mathematical concepts and the limited ability of students to analyze problems systematically. This study suggests that teachers use more varied teaching methods, such as problem-based learning and the use of visual media, to help students overcome these difficulties.